STRATEGI PENGEMBANGAN KAWASAN PACU JALUR SEBAGAI WATERFRONT CITY TELUK KUANTAN (Jurnal Kajian Lingkungan, 2014)
Teluk Kuantan is a capotal city of Kuantan Singingi, regency it has potency of natural resources which can be improved to tourism area, conservation area, residence`area that help economy of people and`also to realize an eternity of environtment. Kuantan river is one of natural resources that can be used to increase economy and people welfane of Teluk kuantan. Kuantan river that belongs of the Teluk Kuantan city.Has an important part in social development, culture, and economy of Teluk Kuantan, that could be a center of govermnent which has the waterfront city konsep. This reserach was intended to know the condition of Kuantan river environment in legal aspek, biophysics aspect, and human society, it has potency of not and what is the problem of pacu jalur area to be waterfront city and to find out the some alternatives development that probably can be performed through optimal and continuosly. Model development is made according to the ecology aspect, culture-social aspect, economy aspek and commite aspect which is used Analytical Hierarchy Processs (AHP). Based on the result of this research, Pacu Jalur area had potency as a waterfront city development. Model development waterfront city can be seen from legal aspect and biophysic that classified into three zone including, natural zone, semi-natural zone, and multi purpose zone. According to AHP assesment, then the alternative strategy development Pacu Jalur area as Teluk Kuantan waterfront city for development of community; development area; revitalisasi river; increasing of coordination stakeholders; law enforcement, and policy socialization.Keywords: Pacu jalur area, waterfront city, Teluk Kuantan